Trade facilitation measures to enhance women's participation in cross-border trade in BBIN - Nisha Taneja; Sanjana Joshi; Shravani Prakash; Samridhi Bimal (Indian Council for Research on International Economic Relations (ICRIER), 2018)
Trade facilitation measures improve the trading environment by reducing transaction costs and thereby increasing the gains from trade. Although the use of trade facilitation measures for tackling trade bottlenecks has gained traction in recent times, one aspect which remains largely unexplored is the importance of gender sensitivity in trade facilitation. The gender dimensions of trade facilitation and logistics have largely been examined in sub-Saharan Africa. In South Asia, however, not much attention has been given to understand the gender impact of services involved in trade facilitation like customs and border management, logistic services, trade infrastructure and transportation. The practice of employing gender differentiated filters on trade policies, port-level procedures, infrastructure planning, and design of trade promotion programs is almost non-existent in South Asia. The neglect of gender specific constraints and impediments within the overall frame of trade facilitation has serious implications not just for women's empowerment but also for productivity and growth potential of these economies. The current paper is part of a systematic initiative to develop an analytical framework to identify the challenges and impediments faced by women in engaging in cross-border trade, with particular emphasis on demonstrating the importance of gender mainstreaming for trade facilitation measures in South Asia. The focus of the study is on the Bangladesh-Bhutan-India-Nepal (BBIN) region - specifically on the North-East region of India and No
Keywords: F10; F15; J16; R49; 330; India; BBIN; Trade Facilitation; Gender